(3GdCfeGW GdbjGOjI hYdGbJgG HGdCOGA GdhXjaj ef hLgI fXQ GdYGedjf aj GdeOGQS GdKGfhjI (B: (3OQGSI ejOGfjI aj HYV KGfhjGJ LHd dHfGf GdQSejIs - (3egfG, Ydj MHjHs ((3HjQhJs (3GdLGeYI GdGSdGejI (B- (3cdjI GdCOGH hGdYdhe GdGfSGfjIs, 2014)
(3JgOa GdOQGSI Edi GdJYQa Ydi GfeGW GdbjGOI GdSGFOI dOi eOjQj GdeOGQS GdKGfhjI aj eMGaXI LHd dHfGf hYdGbJgG HGdCOGA GdhXjaj ef hLgI fXQ GdYGedjf (B( (3fGXQ(B-(3efSb(B-(3eTQa(B-(3eOQS(B) (3hbO GSJNOe GdefgL GdhUaj dedGAeJg ehVhY GdOQGSI hdJMbjb GdCgOGa bGe GdHGMK HGSJNOGe GSJHjGfjf GdChd ehLg Edi GdeOjQjf hGdKGfj Edi GdYGedjf hWHbG Ydi (B20 (3KGfhjI (B( 20 (3eOjQkG h (B200 (3YGemd fSHI (B27 % (3ef GdKGfhjGJ GdQSejI aj eMGaXI dHfGf(B) . (3hbO JhUdJ GdOQGSI Edi YOI fJGFL cGf ef CgegG(B: (3Cf GdfeW GdbjGOj GdOjebQGWj gh GdfeW GdCcKQ eeGQSI ef bHd eOjQj KGfhjGJ LHd dHfGf GdQSejI MjK Ef gPG GdfeW eJhGaQ JeGekG jdjg GdfeW GdbjGOj GdMQ hCNjQkG GdfeW GdbjGOj GdChJhbQGWj(B. (3ceG JhUdJ GdOQGSI Edi hLhO NUGFU JDOj Edi JMSf GdCOGA GdhXjaj hgj(B: (3YOe JbjO GdeOjQjf HGdCfXeI hGdJYdjeGJ GdJj JYjb eHGOQGJ GdYGedjf GdTNUjI dJMSjf COGFge GdhXjaj hYOe GdaJhQ aj GdYdGbGJ GdEfSGfjI, JhajQ GdEecGfjGJ GdeGOjI aj HjFI GdYed, ESJNOGe GdJbfjGJ GdMOjKI, GdTYhQ HGdQVi Yf GdhXjaI, MRe GdbjGOI jSGge aj JMSjf GdcaGAI GdEfJGLjI, JbhjI JahjV GdSdWGJ jSGYO aj JMSjf GdCOGA GdhXjaj dOi GdYGedjf(B. (3hCNQi JDOj Edi JQGLY GdCOGA GdhXjaj hgj(B: (3VYa GdJaGYd Hjf GdeOjQjf hGdYGedjf, fXGe GdGJUGd GdSGFO aj GdbWGY GdYGe, YOe GdeTGQcI aj GJNGP GdbQGQGJ, YOe JYQja GdQYGjI ddYGedjf aj GdbWGY GdYGe, YOe GdMUhd Ydi GdJQbjg aj ehGYjOgG hcTaJ GdOQGSI Cf gfGc YdGbI EjLGHjI Hjf GdfeW GdbjGOj GdOjebQGWj hGdMQ eY GdCOGA GdhXjaj, CeG ajeG jJYdb HGdfeW GdChJhbQGWj aEfg dG jhLO Cj YdGbI eY GdCOGA GdhXjaj(B. (3ceG CXgQJ GdOQGSI Cf GdCOGA GdhXjaj dG jJCKQ HeJZjQGJ GdLfS, GdYeQ, GdeDgd GdYdej, SfhGJ GdNHQI, GdMGdI GdGLJeGYjI, ESe GdhXjaI(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Gestion scolaire; Leadership; Leadership; Public Sector Secondary Education; School management; Secteur Public Cycle Secondaire; (3GdGOGQI GdeOQSjIs; (3GdJYdje GdQSej GdeQMdI GdKGfhjIs; (3GdbjGOI LHd dHfGfs